Numerical modelling of damage to masonry buildings due to tunnelling - Liu, G; Gang Liu (1997)
﻿ Accurate assessment of the damage to buildings due to tunnelling in soft ground becomes an important issue when a tunnel is constructed under historic masonry buildings in urban areas. The current two-stage approach in which settlements estimated from a Gaussian curve are applied to a building does not consider soil-structure interaction and fails to give a correct prediction of the damage. This thesis describes a complete threedimensional finite element model for assessment of the settlement damage to masonry buildings induced by tunnelling in London Clay, and an investigation of the interaction between a masonry building and the ground. A macroscopic elastic no tension model, which assumes the material has zero tensile strength but infinite compressive strength, is developed to simulate the behaviour of masonry. Numerical techniques are proposed to improve the stability of the calculation. The comparison of the no tension and elastic models, by applying Gaussian curve settlement troughs to both a plain wall and a facade, shows that the no tension model predicts different behaviour of the masonry building during tunnelling, including different cracking patterns and damage grades. Two-dimensional finite element analyses combining the building, modelled by the no tension material, and the ground, modelled by a nested yield surface model, give insight into the interaction between the masonry structure and the ground. They suggest the importance of the stresses in the soil prior to the excavation in affecting the ground movements during tunnelling. Thus the weight of the building controls the overall magnitude of the ground movements beneath the building, while the stiffness of the building affects the shape of the trough. A key aspect of the behaviour of the masonry building is the formation of stress arches. Finally the three-dimensional finite element analyses are described. Both symmetric and unsymmetric cases are analysed. The results show that the three-dimensional analysis gives more realistic modelling of the problem and is likely to be necessary for practical situations, especially when a building is not symmetrically located with respect to the tunnel - a case which cannot be analysed in two-dimensions. A special tying scheme is proposed for the connection of the nodes belonging to elements of different types, which are defined in their own local co-ordinate systems. Different types of tie elements are formulated and implemented for connection between two-dimensional and three-dimensional elements in various combinations.